Road Safety Education Courseware: A Study of Satisfaction and Learning Performance among Primary School Students in Malaysia - Zulkifli, Abdul Nasir; Mohamed, Nur Fadziana Faisal; Qasim, Mustafa Moosa; Abu Bakar, Nur Afiqah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
There is a significant increase in road accident statistics in Malaysia and this reflects the culture formed among users related to road safety. In developing a positive road safety culture, road safety education should be introduced from an early age. The effort by the Ministry of Education Malaysia in implementing road safety education in primary schools since 2007 is a wise move towards the formation of that culture. As the road system becomes busier and more complex, children need to be educated with sufficient knowledge and skills to cope with increasingly challenging road situations. This paper introduced the ROSE courseware which incorporates multimedia, AR and VR technologies for the purpose of assisting teachers and students to understand and acquire skills related to road safety. A study was conducted among 30 primary school students in using the ROSE courseware for road safety education. The study provides an insight into the relationship between perceived ease of use, perceived usefulness, and enjoyment and students’ satisfaction in using the ROSE courseware utilising Pearson correlation and regression analyses. Regression analysis resultsindicate the significant relationships between perceived usefulness and enjoyment and students’ satisfaction in using the ROSE courseware. However, the relationship between perceived ease of use and satisfaction is notsignificant.Using paired sample t-test, this study also looked at the students' learning performance due to the intervention of the ROSE courseware for RSE. The outcomes showed that the mean scoredifference between the pre-test and post-test is significant. By using the ROSE courseware, thestudents gained significantly higher level of road safety knowledge which indicates that the learning performance among the participants has been enhanced through the implementation of the ROSE courseware.